Essential Oil of Patchouli Inhalation Exhibits An Anxiolytic-Like Effect in Mice: Elevated Plus-Maze Test - Johansyah, Fadilla Anita Kinksky; Hestianah, Eka Pramyrtha; Rimayanti, Rimayanti; Hidajati, Nove; Santoso, Kuncoro Puguh; Sudjarwo, Sri Agus; Hidayatik, Nanik (Jurnal Medik Veteriner, 2023)
Anxiety disorder is one of the important public health problems. This study aimed to find out whether patchouli (Pogostemon cablin (Blanco) Benth.) essential oil (PEO) has an anxiolytic-like effect in mice. A total of 20 mice were divided into five treatment groups i.e. (C1) was treated with 1 mg/kg of saline intraperitoneally; (C2) was treated with 1 mg/kg of diazepam intraperitoneally; (T1) 1% PEO inhalation, (T2) 2.5% PEO inhalation, and (T3) 5% PEO inhalation. All experimental animals were put in the Elevated Plus-Maze (EPM), observed for five minutes, and investigated the following parameters i.e. the total number of squares that are transverse in the open arms (STO), the number of visits to the open arms (VOA), the number of visits to the closed arms (VCA), the time spent in the open arms (TOA), and the time spent in the closed arms (TCA). In results, T1 and T2 groups had a minor impact on the VOA. T1 group also had little effect on TOA. Closed-arm activities (VCA and TCA) were unaffected by any of the treatments. The conclusion was revealed that T1 or less of PEO inhalation can potentially provide anxiolytic-like effects in mice.